2015
DOI: 10.1002/2015gl063924
|View full text |Cite
|
Sign up to set email alerts
|

New observations of displacement steps associated with volcano seismic long‐period events, constrained by step table experiments

Abstract: Long‐period (LP) volcano seismic events often precede volcanic eruptions and are viewed with considerable interest in hazard assessment. They are usually thought to be associated with resonating fluid‐filled conduits although alternative models involving material failure have recently been proposed. Through recent field experiments, we uncovered a step‐like displacement component associated with some LP events, outside the spectral range of the typically narrow‐band analysis for this kind of event. Bespoke lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The geometry of the tensile cracks found through MTI is superimposed onto the relocated structure, revealing en echelon fractures within Turrialba's edifice. In combination with results from previous studies [Eyre et al, 2015;Thun et al, 2015], we suggest that this structure could be a response to the deformation of the shallow part of the edifice [Bean et al, 2014], with a shearing band together with high fluid pressure inducing tensile fractures at The obtained relocation structure, when combined with the source mechanisms obtained through MTI, reveals a detailed geometrical relationship between LP sources, which can be interpreted with respect to a new, recently proposed brittle deformation-based LP source model. This study therefore highlights the need for further LP event studies to implement a more systematic relocation procedure, together with joint interpretation of the source mechanisms, to better infer the source processes of LP events within volcanoes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The geometry of the tensile cracks found through MTI is superimposed onto the relocated structure, revealing en echelon fractures within Turrialba's edifice. In combination with results from previous studies [Eyre et al, 2015;Thun et al, 2015], we suggest that this structure could be a response to the deformation of the shallow part of the edifice [Bean et al, 2014], with a shearing band together with high fluid pressure inducing tensile fractures at The obtained relocation structure, when combined with the source mechanisms obtained through MTI, reveals a detailed geometrical relationship between LP sources, which can be interpreted with respect to a new, recently proposed brittle deformation-based LP source model. This study therefore highlights the need for further LP event studies to implement a more systematic relocation procedure, together with joint interpretation of the source mechanisms, to better infer the source processes of LP events within volcanoes.…”
Section: Discussionsupporting
confidence: 75%
“…Similar models have been proposed by, e.g., Jousset et al [2013] on Merapi volcano. However, Thun et al [2015] showed that the LP events used here contain a significant static displacement component. This observation is not consistent with a pure resonance mechanism.…”
Section: Discussion: Relationship Between Source Locations and Mechanmentioning
confidence: 81%
“…The sources inferred above would theoretically cause total static displacements smaller than 1 µm at the next closest station, DY1. Sub-micrometre steps are not detectable with our instruments and methods14. The fact that the events are not visible at the other stations also implies that the dynamic seismic signals, i.e.…”
Section: Experiments and Data Analysismentioning
confidence: 67%
“…As high-frequency waves are attenuated strongly when travelling through the ground, such high frequencies thus indicate a fracturing process close to the station. In a recent study14, we presented a new data processing approach that allows for the recovery of micrometre-scale displacement steps from instrument-corrected seismograms. It is based on long-period noise removal using median filters and its performance was confirmed by laboratory experiments.…”
Section: Experiments and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation